EFEKTIVITAS DIET JUS TOMAT UNTUK MENURUNKAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI SELOGIRI KABUPATEN WONOGIRI - Nugroho, Yohanes Wahyu; Nuasirina, Linta Widi (Akademi Keperawatan Giri Satria Husada Wonogiri, 2019)
Background : Hypertension is a disorder of the circulatory system which is quite disturbing to public health, this is due to non-tangible symptoms which are often fatal and if not treated immediately can cause damage to organs in the body such as the heart, kidneys, eyes and vessels blood.Tomato fruit is the most nutritious part to cure diseases, one of which is high blood pressure. The most important compounds are solanine alkaloids, saponins, folic acid, malic acid, citric acid, sugar (glucoa, fructose), adenine, trigonelin, kholin, tomatin, and histamine which can overcome high blood pressure in hypertension.Objective : Obtained real experience and effectiveness of tomato juice diet to reduce blood pressure in patients with hypertension to overcome the problem of high blood pressure.Method : Descriptive case study which is one type of strategy in qualitative research, with a case study research approach. From several respondents, the authors only took 20 respondents to be used as case studies.Results : From the study found an average decrease systolic blood pressure of group experiment was 9,6 mmHg with standard deviation 0,843 and diastolic was 5,2 mmHg with standard deviation 1,229. Result Paired Sample T Test of experiment group is p<0, 05, indicating a tomato juice can lower blood pressure. In the Independent T Test values obtained significance p<0,05, which means there is significant difference in blood pressure reduction between experiment group and control group. Patients with hypertension are advised to consume tomato juicefor high blood pressure treatment.